2013
DOI: 10.1016/j.brachy.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Focal high-dose-rate brachytherapy: A dosimetric comparison of hemigland vs. conventional whole-gland treatment

Abstract: PURPOSE: To determine the utility of focal high-dose-rate brachytherapy for localized prostate cancer, we investigated the impact on target coverage and dose to organs at risk (OARs) with hemigland (HG) compared with whole-gland (WG) treatment. METHODS AND MATERIALS:A total of 10 WG implants were used to generate 10 WG and 20 HG (left and right) treatment plans optimized with the inverse planning simulation annealing algorithm using Oncentra MasterPlan (Nucletron B.V., Veenendaal, The Netherlands). The standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…As the uncertainties in brachytherapy being reduced, many new hypofractionation and focal tumor boost protocols have been developed. 111 113 Hypofractionated HDR mono-therapy for prostate cancer has been gaining more attention from investigators, not only because of reduced in-hospital time for the patient, but also because of the low α/β ratio (1 to 2 Gy) of prostate cancer. Prada et al reported using treatments of a single HDR fraction of 19 Gy for patients with favorable prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As the uncertainties in brachytherapy being reduced, many new hypofractionation and focal tumor boost protocols have been developed. 111 113 Hypofractionated HDR mono-therapy for prostate cancer has been gaining more attention from investigators, not only because of reduced in-hospital time for the patient, but also because of the low α/β ratio (1 to 2 Gy) of prostate cancer. Prada et al reported using treatments of a single HDR fraction of 19 Gy for patients with favorable prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our default inverse planning simulated annealing optimization solution was used and manual graphical optimization was used to finetune the final plans (5). Patients were treated with 7.25 Gy  6 fractions using a standard WG catheter distribution.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of focal therapy research at this time is exploring the efficacy and safety of various non-radiation treatment modalities including cryotherapy, high-intensity focused ultrasound, laser ablation, and photodynamic therapy (5,6). Much less work is published on focal therapy using radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Hemigland dosimetric assessment revealed effective target coverage, and doses to the rectum, bladder, and urethra were reduced significantly. The degree of reduction in the dose to 2cc to these organs was from 64.1%–53.1% for the rectum, 67.5%–55.9% for the bladder, and 95.2%–69.3% to the urethra 10. The addition of a focal radiation boost by stereotactic radiation or HDR brachytherapy to a course of whole-gland external beam radiation has also been studied 1113.…”
Section: Focal Therapy Experiencementioning
confidence: 99%
“…Much of the experience with a focal approach in itself has been seen with ablative techniques that include high-intensity focused ultrasound (HIFU) and cryotherapy. Other, less-studied partial approaches to deliver radiotherapy include hemigland high-dose rate (HDR) brachytherapy10 and a focal boost to a course of whole-gland radiation. In the latter experiences, the focal boost has been delivered with differential dose external beam radiation, differential HDR brachytherapy, and LDR brachytherapy 1114…”
Section: Introductionmentioning
confidence: 99%